Implementasi Terapi Kognitif untuk Meningkatkan Harga Diri pada Remaja yang Mengalami Bullying dengan Masalah Keperawatan Harga Diri Rendah di Desa Kauman Kota Kediri (Studi Kasus) - Rahmadaniar, Anjar Farah; Risnasari, Norma; Prihananto, Dhian Ika (Lembaga Publikasi Ilmiah Nusantara, 2025)
Bullying is an aggressive behavior that is carried out repeatedly by a person or a group of people towards a vulnerable victim with the intention of intimidating, threatening, or belittling the victim. Bullying can occur in various forms, such as physical bullying, verbal bullying, social bullying, and cyberbullying. The purpose of this study is to analyze the level of self-esteem in adolescents who experience bullying with low self-esteem nursing problems before and after cognitive therapy. This study is descriptive in nature, using a case study approach method. The subjects used in this study were 2 adolescents who experienced bullying, which was measured through a questionnaire. Intervention was carried out through the provision of cognitive therapy for three days. The results of the study showed a significant increase. Cognitive therapy is widely recognized as one of the most effective therapeutic approaches and is supported by empirical evidence for various psychological problems, including depression, anxiety, and low self-esteem. This researcher recommends conducting cognitive therapy to increase motivation and improve the mental well-being of adolescents.